Pengaruh Gaya Hidup Dan Literasi Keuangan Terhadap Perilaku Keuangan Mahasiswa Manajemen Fakultas Ekonomi Dan Bisnis Universitas Trunojoyo Madura - Syamsiyah, Siti Nur; Purnomo, Arie Setyo Dwi (Management Department of Economics and Business Of Trunojoyo Madura University, 2025)
The purpose of this study was to determine the effect of Lifestyle and Financial Literacy on the Financial Behavior of Management Students at the Faculty of Economics and Business, Trunojoyo Madura University, class of 2019 to class of 2022. This research was conducted using associative quantitative methods. The analysis used in this study was multiple linear analysis. The data used in this study are primary and secondary data, primary data is data obtained from questionnaires distributed to respondents and secondary data is data obtained from the Administration office. The sampling technique used the Slovin sampling method and obtained a total sample of 92 respondents. The hypothesis testing used is multiple regression analysis with the SPSS 25 program. The results of the T test show that lifestyle has a significant effect on financial behavior with a significant value of 0.000 0.05, financial literacy has a significant effect on financial behavior with a significant value of 0.005 0. 05. And the results of the F Test show that Lifestyle and Financial Literacy have a simultaneous (simultaneous) effect on financial behavior with a sig p-value of 0.000 0.05. The coefficient of determination ( ) is 0.206 or 20.6% and the remaining 79.4% is influenced by other factors that are not included in this research model. Based on the data normality test, the multicollinearity test and the heteroscedasticity test were not found to be variables that deviate from the classical assumption test.